습분분리기 압력강하 상사법칙 개발에 대한 실험적 연구 - 김기환(Kih-Wan Kim); 김우식(Woo-Shik Kim); 이재봉(Jae-Bong Lee) (동력시스템공학회지, 2020)
증기발생기 습분분리기의 압력강하는 원자력발전소의 효율과 습분분리기 설계에 있어 중요한 설계변수이다. 본 연구에서는 실 스케일의 습분분리기 물/증기 조건을 모의하기 위하여 저압에서 운영되는 물/공기 실험장치를 구축하였다. 상사법칙에 기반한 실험방법론이 본 연구에서 제안되었으며 본 물/공기 실험장치를 이용하여 질량건도가 0.269-0.538의 범위에서 압력강하를 측정하였다. 본 연구에서 측정한 결과는 실제 조건의 결과와 비교하여 결과를 검증하였다. 실험결과 점성비와 이상유동 원심력이 압력강하에 미치는 주요 인자로 확인되었다. The pressure drop of the moisture separator in a steam generator is the important key parameter to design the moisture separator and ensure the efficiency of a nuclear power plant. In this research, the low presuree air/water test facility was constructed to simulate the steam/water condition for the full-scale moisture separator. The experimental method based on the simiairty law was presented and the pressure drop was measured for a mass quality ranged from 0.269 to 0.538 using the air/water test facility. The otbained results were verified by comparing with the results of the prototype condition. It is discovered that the viscosity ratio and two-phase centrifugal force are the factors influencing the pressure drop. KCI Citation Count: 0